The custom-fit workplace : choose when, where, and how to work and boost your bottom line - Blades, Joan.; Fondas, Nanette, 1959- (San Francisco, CA : Jossey-Bass, 2010)
"With The Custom-Fit Workplace, Blades and Fondas offer an indispensable handbook for business professionals that will transform the way we work, highlighting proven best practices for breaking free from the old, inflexible, 40-hour schedule. The authors know that change is afoot in businesses across America and throughout the world: Dual earning households continue to grow in record numbers; men and women are taking time off from their careers to take care of children or aging parents and are struggling to find a way back in; our 24/7 work culture is placing an undue burden on working professionals; and workers everywhere are struggling to balance career and personal lives while making ends meet. At the same time, businesses hit hard by the economic crisis are looking for creative ways to retain their talent rather than laying off people to make their numbers. We are, in short, standing on the precipice of a workplace revolution, and The Custom-Fit Workplace will be the definitive roadmap that explains how to navigate the changing landscape. Featuring compelling stories of companies like Jet Blue, Ernst & Young, Best Buy, Deloitte & Touche, and the University of California, the book will profile strategies that are already gaining traction in workplaces across the country, such as: new twists on traditional flexible hours and part-time work strategies; work from home and staffing entirely at-home workers; results-only work environments (ROWEs); babies at work programs; "on ramp" and "off ramp" opportunities. Individuals will learn creative ways to integrate their work requirements with their life obligations, while managers will be persuaded to adopt these flexible work strategies to improve their bottom line by tapping into the power of their most important asset: their people. Every reader will finish the book convinced of the place of flexible work arrangements in the twenty-first-century workplace, and walk away with an expanded tool set to use in his or her own work environment. An eminently practical and engaging researched-based book, The Custom-Fit Workplace will provide individuals and employers everywhere the tools they need to be successful and happy both at work and in their other life pursuits"--
Includes bibliographical references and index.
Keywords: Flexible work arrangements; Work -- Social aspects; Quality of work life